2018
DOI: 10.4049/jimmunol.1800950
|View full text |Cite
|
Sign up to set email alerts
|

Aire Controls in Trans the Production of Medullary Thymic Epithelial Cells Expressing Ly-6C/Ly-6G

Abstract: Medullary thymic epithelial cells (mTECs), which express a wide range of tissue-restricted Ags (TRAs), contribute to the establishment of self-tolerance by eliminating autoreactive T cells and/or inducing regulatory T cells. Aire controls a diverse set of TRAs within Aire-expressing cells by employing various transcriptional pathways. As Aire has a profound effect on transcriptomes of mTECs, including TRAs not only at the single-cell but also the population level, we suspected that Aire (Aire+ mTECs) might con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…mTECs are classified into immature mTECs (CD80 low mTECs) and mature mTECs (CD80 high mTECs) based on the expression levels of CD80 (23,24). By using the mAbs specific for Ly6C (clone HK1.4) and Ly6G (clone 1A8), we have demonstrated that Ly6C 1 /Ly6G À , Ly6C À /Ly6G 1 , and Ly6C 1 /Ly6G 1 subsets of mature CD80 high mTECs exist with various proportions depending on the genetic background of mice (i.e., 515% in total) (21). These Ly6C-and/or Ly6G-expressing mTECs localized preferentially at the cortico-medullary junction and expressed high levels of tissue-restricted self-antigens and thymocyte-attracting chemokines.…”
Section: Dispensable Role Of Ly6c Proteins In Immune Homeostasismentioning
confidence: 99%
See 2 more Smart Citations
“…mTECs are classified into immature mTECs (CD80 low mTECs) and mature mTECs (CD80 high mTECs) based on the expression levels of CD80 (23,24). By using the mAbs specific for Ly6C (clone HK1.4) and Ly6G (clone 1A8), we have demonstrated that Ly6C 1 /Ly6G À , Ly6C À /Ly6G 1 , and Ly6C 1 /Ly6G 1 subsets of mature CD80 high mTECs exist with various proportions depending on the genetic background of mice (i.e., 515% in total) (21). These Ly6C-and/or Ly6G-expressing mTECs localized preferentially at the cortico-medullary junction and expressed high levels of tissue-restricted self-antigens and thymocyte-attracting chemokines.…”
Section: Dispensable Role Of Ly6c Proteins In Immune Homeostasismentioning
confidence: 99%
“…Thymic epithelial cells (TECs) were prepared via enzymatic digestion of thymi, and subjected to flow cytometric analysis using a FACSCalibur (BD Biosciences) and a FACSAria II (BD Biosciences) as described previously (21,23,24). In brief, TECs were defined as CD45 À epithelial cell adhesion molecule 1 (EpCAM) 1 cells, and mTECs were defined as CD45 À EpCAM 1 Ulex europaeus agglutinin 1 (UEA-1) 1 cells.…”
Section: Cell Preparation and Flow Cytometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Foxp3/Transcription Factor Staining Buffer Set (Invitrogen) was used for the staining of Aire, CTLA-4 and Foxp3. Flowcytometric analysis was performed using a FACSAria II (BD Biosciences) as described previously (Morimoto et al, 2018). The data were analyzed using FLOWJO 10.7.1 software (TreeStar Software) or BD FACSDiva software (version 8.0) (BD Biosciences).…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…Reaggregate thymic organ culture (RTOC) was performed as previously described (Morimoto et al, 2018). Briefly, thymic lobes from E15.5 to E16.5 fetuses from WT or Aire-KO were cultured on nucleopore filter (Whatman) placed in R10 containing 1.35mM 2-deoxyguanosine (2-DG) (Sigma) for 6 days.…”
Section: Reaggregate Thymic Organ Culturementioning
confidence: 99%